2021
DOI: 10.1038/s41467-021-24249-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration guided by long-lived spatial memory

Abstract: Living cells actively migrate in their environment to perform key biological functions—from unicellular organisms looking for food to single cells such as fibroblasts, leukocytes or cancer cells that can shape, patrol or invade tissues. Cell migration results from complex intracellular processes that enable cell self-propulsion, and has been shown to also integrate various chemical or physical extracellular signals. While it is established that cells can modify their environment by depositing biochemical signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 68 publications
5
68
0
Order By: Relevance
“…S3) PDMS microtubes. These observations suggested that CeR may not be sensitive to ECM components although substrate coating could be modified by cell-induced reorganization of the matrix ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…S3) PDMS microtubes. These observations suggested that CeR may not be sensitive to ECM components although substrate coating could be modified by cell-induced reorganization of the matrix ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…This class of self-interacting random walks has clear applications in a broad range of examples where a random walker modifies locally its environment -leaving behind footprints along its path, and in turn responds to its own footprints [28,29]. Such behaviours have been reported for ants depositing pheromones along their path [30], larger territorial animals [31], and have been identified quantitatively in the case of living cells that chemically modify and remodel the extra-cellular matrix [32,33].…”
Section: Introductionmentioning
confidence: 94%
“…The search process starts at t = 0, but the random walker is assumed to have explored the domain from t = −T to t = 0. S(t) is the survival probability of the random walker at time t. The scaling of S(t) with geometrical parameters is deduced from (30) and (32), for compact and non-compact processes respectively. The collapse of numerical simulations after rescaling captures the dependence of the FPT distribution on geometrical parameters.…”
Section: B Search Efficiency Of Self-interacting Random Walkersmentioning
confidence: 99%
“…1 To mimic natural cell distribution and to study cell migration and communication, the spatial control of cell-attachment (cell patterning) is of great interest. [2][3][4] The most frequently used approaches for cell-patterning focus on controlling the stiffness and texture of substrates or the position of cell attractive molecules on inorganic substrates or biomaterials. 2,[5][6][7][8] However, these methods usually lack spatiotemporal control of the morphology of the cellular environment, which plays an essential part in natural matrices that are constantly reshaped by various stimuli.…”
Section: Introductionmentioning
confidence: 99%